1992
DOI: 10.1116/1.577904
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy study of the stability of Fomblin Z25 on the native oxide of aluminum

Abstract: Thin films of Fomblin Z25, a perfluoropolyalkylether lubricant, were vapor deposited onto clean, oxidized aluminum, and sapphire surfaces, and their behavior at different temperatures was studied using x-ray photoelectron spectroscopy and temperature desorption spectroscopy (TDS). It was found that the interfacial fluid molecules decompose on the native oxide at room temperature, and continue to decompose at elevated temperatures, as previous studies had shown to occur on the clean metal. TDS indicated that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[ 32 ] The peak positions of F 1 s at 685.9 and 687.2 eV are respectively attributed to the presence of LiF and AlF 3 in the composite. [ 33 ] For the Al 2 p spectrum, the peak appears at 76.8 eV which is attributed to AlF 3 . [ 34 ] These results confirm that the deep eutectic reaction forms a halide composite with LiCl, LiF, AlF 3 , and Ga–Cl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] The peak positions of F 1 s at 685.9 and 687.2 eV are respectively attributed to the presence of LiF and AlF 3 in the composite. [ 33 ] For the Al 2 p spectrum, the peak appears at 76.8 eV which is attributed to AlF 3 . [ 34 ] These results confirm that the deep eutectic reaction forms a halide composite with LiCl, LiF, AlF 3 , and Ga–Cl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…21 While PFPEs are stable in an inert atmosphere up to 410 C and to approximately 316 C in an oxygen-rich environment, they are catalytically decomposed by metals and Lewis acids at lower temperatures. [22][23][24] Ab initio calculations of peruorodiethylether ((CF 3 CF 2 ) 2 O) as model systems to PFPEs concluded that protonation via Lewis acids at all sites (uorine and oxygen atoms) is energetically favorable.…”
Section: 13mentioning
confidence: 99%
“…21 While PFPEs are stable in an inert atmosphere up to 410 C and to approximately 316 C in an oxygen-rich environment, they are catalytically decomposed by metals and Lewis acids at lower temperatures. [22][23][24] Ab initio calculations of peruorodiethylether ((CF 3 CF 2 ) 2 O) as model systems to PFPEs concluded that protonation via Lewis acids at all sites (uorine and oxygen atoms) is energetically favorable. 25 Therefore, it is probable that decomposition is not totally due solely to acid-mediated reactions with the polyether oxygen as previously believed, but may also involve reaction with uorine and the possible formation of HF as an excellent leaving group.…”
Section: Introductionmentioning
confidence: 99%